The Relationship Between Age and Parity With the Incidence of Chronic Energy Deficiency (KEK) in Pregnant Women - Listiana, Akma; Jasa, Novi Eniastina (Universitas Islam Lamongan, 2022)
The World Health Organization (WHO) estimates that worldwide more than 585,000 women die each year during pregnancy or childbirth. The maternal mortality rate is used as an indicator to describe the level of awareness of healthy living behavior, nutritional problems and maternal health. Nutritional problems that commonly occur in pregnant women are nutritional deficiencies, both macro and micro nutritional deficiencies which are manifested in chronic energy deficiency status (KEK). Chronic Energy Deficiency (KEK) is a condition in which the mother suffers from chronic (chronic) food shortages, causing health problems for pregnant women. (Paramashanti, 2021). The average prevalence of pregnant women who experience CED in the world is 15-47% (WHO, 2012). Indonesia is a country that has moderate category of public health problems (5-9.9%) for pregnant women at risk of KEK. (Riskesdas, 2018).The design of this research is analytic with cross sectional approach. The population in this study were all pregnant women who had their pregnancy checked at PMB. Wirahayu in January-August 2022 totaled 430 people. The sample taken is the entire population of 430 people. Data analysis techniques are univariate and bivariate. Based on the results of research from 430 pregnant women, it was found that 83 pregnant women (19.3%) experienced CED. Statistical test results obtained p-value 0.015, this means that there is a relationship between parity to the incidence of KEK. Based on the age of the respondent, the results of the statistical test obtained a p-value of 0.000, which means that there is a relationship between maternal age and the incidence of KEK.In this study, because there are still many KEK incidence rates, regardless of parity and maternal age, it is better if pregnant women during ANC are given explanations, leaflets and descriptions of the dangers of Chronic Energy Deficiency (KEK), so that mothers can understand the impact of KEK.